INTERVENTIONAL MR SYSTEMS - Hajab Sagher Almutairi, Mohammed Muraizeeqalotaibi, Fahad Matar Rashid AL Mutairi, Abdul karimmatar almutiri (Chelonian Research Foundation, 2022)
This research paper is aimed at explaining the technology of interventional magnetic resonance imaging or iMRI. The technique has been described in detail followed by different varieties and examples of iMRI applications. In the next section, the advancements in this field have been discussed with special reference to magnetic resonance or MR compatible instruments and ongoing research on augmented reality (AR). However, the target being real time imaging all during a surgical operation, there still appear to be several challenges. The most critical challenges in using this technique have thus been discussed followed by a conclusion. Keywords: Interventional MR, iMRI, intraoperative MRI, MRI, Magnetic Resonance, Operating Room, imaging